2001
DOI: 10.1007/s004250000468
|View full text |Cite
|
Sign up to set email alerts
|

Non-photosynthetic enhancement of growth by high CO 2 level in the nitrophilic seaweed Ulva rigida C. Agardh (Chlorophyta)

Abstract: The effects of increased CO2 levels (10,000 microl l(-1)) in cultures of the green nitrophilic macroalga Ulva rigida C. Agardh were tested under conditions of N saturation and N limitation, using nitrate as the only N source. Enrichment with CO2 enhanced growth, while net photosynthesis, gross photosynthesis, dark respiration rates and soluble protein content decreased. The internal C pool remained constant at high CO2, while the assimilated C that was released to the external medium was less than half the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
141
4
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 20 publications
20
141
4
5
Order By: Relevance
“…This is in accordance with previous studies carried out under elevated CO 2 [47][48][49][50]. Plants lose the ability to take up soil nitrate (most common form of nitrogen) and convert it into organic compounds such as proteins at enriched CO 2 conditions.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with previous studies carried out under elevated CO 2 [47][48][49][50]. Plants lose the ability to take up soil nitrate (most common form of nitrogen) and convert it into organic compounds such as proteins at enriched CO 2 conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in our system, nutrients are the key driver of C:N ratios in Ulva and Fucus. While we observed higher concentrations of N within Ulva tissues grown under high pCO 2 treated individuals, the difference was not significant and our results do not match Gordillo et al (2001) and Xu and Gao (2012), who found that high pCO 2 facilitates nitrate uptake in U. rigida and U.…”
Section: Algal Tissue Contentcontrasting
confidence: 99%
“…or Fucus vesiculosus. Although adding carbon is counterintuitive to decreasing the C:N ratio, Gordillo et al (2001) found that increased pCO 2 resulted in increased uptake of nitrate in U. rigida, thus lowering the tissue C:N ratio. While our results don't show decreased C:N with high pCO 2 , analysis of Ulva tissues grown in biculture and under high pCO 2 show an uptick in nitrogen concentration.…”
Section: Algal Tissue Contentmentioning
confidence: 93%
See 1 more Smart Citation
“…High CO 2 and/or dissolved inorganic carbon (DIC) conditions stimulate growth and photosynthesis of different non-calcifying seaweeds (Gordillo et al 2001, Nygård and Dring 2008, Wu et al 2008, Olischläger et al 2012, Saderne 2012, Koch et al 2013). In addition to the effect of enhanced CO 2 on growth and photosynthesis of seaweeds, reproduction may be impacted by the DIC concentration in seawater.…”
Section: Reproduction Under Ocean Warming and Acidificationmentioning
confidence: 99%